Association of health determinants and depressive symptoms with tooth loss in the Serbian adult population: a cross-sectional study - Čanković, Dušan; Čanković, Miloš; Ukropina, Snežana; Mijatović Jovanović, Vesna; Čanković, Sonja (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Oral diseases appear to be the major risk factors for tooth loss, but social factors and other determinants could play an important role as well. The aim of this study was to determine whether the possible independent sociodemographic risk factors and depressive disorders could contribute to the tooth loss in the adult population of Serbia. Methods. This cross-sectional study analysed the 2013 National Health Survey results for the population of Serbia (without the data for Kosovo and Metohia population). The sample was selected to provide the statistically reliable estimates at the national level. Study included 13,519 adults of 20 years of age, or above. The mean age of participants was 49.9 years including 6,998 (51.8%) females and 6,518 (48.2%) males. The number of missing teeth was dependent variable while the independent variables were: gender, age, marital status, education, employment status, Wealth Index, smoking status, body mass index (BMI), milk and milk products intake, fruit intake excluding juices, vegetable and salad intake (excluding potato), and depression. To measure the current depression, the standardized and validated the Patient Health Questionnaire (PHQ)-8 score was used. Edentulism (complete or partial) was defined as a loss of natural teeth. In order to determine the predictors of tooth loss, the bivariate and multivariate logistic regression models were implemented for all types of tooth loss. Results. The significant differences were observed among the categories of edentulism in relation to independent variables except vegetable and salad intake. The prevalence of all missing teeth was highest in the females, the respondents with a low level of education, inactive, underweight (BMI < 18.5) and respondents with moderately severe depressive episodes (PHQ-8 score 15 to 19). In the multivariate model, we found that the demographic factors (age, living with a partner), socioeconomic factors (primary and secondary education, Wealth Index), smoking, BMI, the PHQ-8 score and the depressive symptoms were significantly associated with partial tooth loss. Conclusion. Study demonstrated that sociodemographic and lifestyle factors as well as the symptoms of depresssion are also important factors related to the tooth loss. This study can help to advance the need for health programs focusing on education, smoking cessation, dietary habits as well as regular visits to the dentist.